Leadership in academic and public libraries a time of change - Duren, Petra (Chandos information professional series, 2013)
In a time when libraries have to face constant change, this book provides examples and advises on how to lead when change is needed (for example, when quality management is implemented or when libraries have to merge or to relocate). Engaging with how constant change affects leadership in libraries and how leaders in libraries act in times of change, this book is aimed at practitioners and students of Library and Information Science (LIS) alike, and is based on both theory and expert interviews from leaders in academic and public libraries that are in the midst, or are now coming out of a process of change. Readership: Staff at all managerial levels within academic and public libraries, as well as bachelor and master students of Library and Information Services